Inclusive Business Models in Coffee Value Chain: Comparing Practical Evidence Between East Java and North Sumatera - Heti Mulyati; Dikky Indrawan (Jurnal Manajemen & Agribisnis, 2021)
This paper explores inclusive business practices by focusing on the relationship between investments for-profit and social impact for small-scale farmers. Value chain mapping was used and combined with business model canvas to enable fact-finding and linkage between profit-taking action and social impact in the coffee value chain. The study was performed in two regions: East Java and North Sumatra. The study interviewed 72 farmers from Bondowoso District, East Java, and 30 farmers from Mandailing Natal District, North Sumatra. The qualitative analysis revealed the role of local organization networks in supporting the extension and improving performance in value chain governance. The organization networks supported social issues and provided access to diverse resources and environments for companies to build commitments. Furthermore, the business model canvas modeled value propositions that were practically tackling the dimensions of profit and social impact to the organization's context. The coffee value chains in both regions were differ based on key features and elements of small farmers' inclusion in the coffee value chain. The findings show that the coffee business model in Mandailing Natal encouraged smallholder farmer inclusion better than in Bondowoso. Therefore, the study implies that a shifting from profit into social initiatives in inclusive business is needed. This study provides practical evidence of business model canvas in the coffee value chain cases, showing how to develop a mission social innovation in a profit organization. Keywords: inclusive business models, business model canvas, value chain, coffee